Dialog Antar-Agama dengan Imersion: Dari Perjumpaan Menuju Kerja Bersama - Widiyono, A. Nugraha (Jurnal Orientasi Baru, 2006)
This article is presented based on immersion experience during workshop on inter-cultural and inter-religious dialogue run by Jesuit School of Theology of Berkeley and Sanata Dharma University of Yogyakarta on January 8th-22nd, 2006 in Yogyakarta. Encountering people from different cultural and religious background purifies our understanding about "other people". We learned that an immersion program is highly helpful to start an inter-religious and intercultural dialogue. An immersion has freed us from our unhealty suspicions and helped us to understand deeply people from other religion. At least, the immersion gave us an opportunity to cultivate our faith and come to positive attitudes towards people from different faith and culture. Accordingly, the purpose of dialogue is not merely for creating a harmonious situation but further to give us an opportunity to advance cooperation among people of different religious experiences.